Numerical simulation of two-phase gas-liquid flows in inclined and vertical pipelines - Loilier, P. (Cranfield University, 2006)
The present thesis describes the advances made in modelling two-phase flows in inclined pipes using a transient one-dimensional approach. The research is a developement of an existing numerical methodology, capable of simulating stratified and slugging two-phase flows in horizontal or inclined single pipes. The aim of the present work is to extend the capabilities of the approach in order (i) to account for the effect of the pipe topography in the numerical solution of the two-fluid model, and (ii) to simulate vertical bubbly twophase flows at various pressures in large diameter pipes, and (iii) to model stratified and terrain-induced slugging in two-phase flow pipelines made of several uphill, downhill and level sections. A transient compressible two-fluid model based on the one-dimensional form of the mass and momentum conservation equations for the gas and liquid phases, is developed to predict those flow configurations. The wall to fluid and the interphase interactions are accounted for by constitutive relations which are flow regime dependent. The conservation equations are discretized using a finite volume method. An algorithm is created to enable simulations on pipelines made of several sections, and account for the effect of the topography in the simulations. The methodology is applied to the compressible model in order to evaluate the robustness and accuracy of the numerical schemes, especially for the high-resolution Advection Upwinding Splitting Method (AUSM) associated to the compressible model. It also assesses the ability of the method to predict three physical flow regimes, namely stratified, bubbly and terrain-induced slug flows. The terrain-induced slugging study is performed on a slightly inclined (±1.5°) V-section system. The use of hydrodynamic slug correlations for hilly-terrain slugging is discussed. It shows to be conclusive with a good agreement with experimental measurements obtained for slug frequency and slug length predictions. Mechanisms such as the wave formation at the interface, the slug growth and propagation as well as merging slugs, can also be observed by the model. The bubbly model is extensively tested against available data collected by Nottingham University from experimental systems of 70mm and 189mm vertical pipes. In some cases, void fraction predictions are within 10% with experimental data, and pressure predictions within 4%. The simulation results compare well in overall with the measurements. In large diameter pipes, some variations are observed between the numerical and the measured results: especially the model underpredicts the flow at the bottom of the pipe. Limitations of the model for this particular case are highlighted. It is also observed that, in fully-developed flows, the model does give satisfactory predictions.